Decontamination effects of the corona discharge with plane to bent needle configuration - Bujaček, K.; Fantova, V.; Kříha, V. (Вопросы атомной науки и техники, 2012)
The dependency of the inhibition zone size on the needle geometry and angle between needle and plane in plane to needle electrode configuration was studied. Needles bent at angles from 0° (straight one) to 90° were used to study both negative and positive corona discharge treatment of the surface contaminated with Candida albicans yeasts.Inhibition zones shape and size changes were studied for positive and negative corona discharge. Ellipsoidal shape was characteristic for all treated samples in case of positive corona treatment, while the three-segment shape was observed for higher angles in case of negative corona discharge.